Pengaruh Gaya Belajar Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Bahasa Indonesia - Adha, Suciarti Nur; Hetilaniar; Syska Purnama Sari (Global Action and Education for Society, 2025)
This research is motivated by the lack of critical thinking skills of students in Indonesian language subjects at SD Negeri 07 Palembang. The purpose of this study was to determine the influence of learning styles on students' critical thinking skills in Indonesian language subjects. The research method used in this study is a quantitative correlational approach. The sample of this study was class V B SD Negeri 07 Palembang as many as 22 students in the 2025 academic year. The instrument used was a questionnaire, with normality and homogeneity that had been tested using SPSS 25 with the results of data analysis showing that the data was normally distributed and homogeneous. Hypothesis testing using the t-test obtained a T-count value of 5.632> T-table 2.704 at the 0.05 level so that Ho was rejected and Ha was accepted. This means that there is a significant influence between learning styles on students' critical thinking skills in Indonesian language subjects. So that learning styles can be used as an alternative to determine students' critical thinking skills.